Vector calculus - Marsden, Jerrold E.; Tromba, Anthony (W.H.Freeman and Company, 2003)
This text helps students foster computational skills and intuitive understanding with a balance of theory, applications and optional materials. This edition offers revised coverage in several areas and a new section looking at applications to differential geometry, physics and forms of life